2020
DOI: 10.1016/j.jclepro.2019.118401
|View full text |Cite
|
Sign up to set email alerts
|

A theory-driven identification and ranking of the critical success factors of sustainable shipping management

Abstract: Sustainable shipping management is arguably the most challenging issue that shipping companies faced for the coming years. Hence, examining the critical success factors of sustainable shipping management is vital. Although previous research mainly focused on the motives and implication of sustainable shipping management, practical research that proposes how sustainable shipping management can be implemented is still lacking. Therefore, this study fills the gap by identifying and ranking the critical success fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 78 publications
(51 reference statements)
0
35
0
Order By: Relevance
“…Moreover, previous studies have developed and implemented different methods and tools, e.g., assessment tools [74][75][76], identification approaches [46,66,[77][78][79], classification methods [80][81][82], etc., to investigate the CSFs of a construction project. Other studies identified the CSFs of construction projects by the certain construction project delivery methods (PDM) which determine each stage in the life cycle, including design, construction and maintenance and required a clear definition of responsibilities of each project participant [14,46].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, previous studies have developed and implemented different methods and tools, e.g., assessment tools [74][75][76], identification approaches [46,66,[77][78][79], classification methods [80][81][82], etc., to investigate the CSFs of a construction project. Other studies identified the CSFs of construction projects by the certain construction project delivery methods (PDM) which determine each stage in the life cycle, including design, construction and maintenance and required a clear definition of responsibilities of each project participant [14,46].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study of Tran et al [65] investigates and ranks the critical success factors (CSF) of sustainable shipping management (SSM) by utilizing a fuzzy analytic hierarch process. The analysis showed that (1) the stakeholders' focus, (2) the intra-firm management, (3) new technology acceptance, (4) the inter-firm collaboration, and (5) the strategic fit are the factors of high importance in descending order.…”
Section: Global Maritime Emission Trading System (Mets)mentioning
confidence: 99%
“…Sustainable shipping is an active topic due to the hottest discussion of GHG, which has recently attracted increasing focuses of both practitioners and researchers due to its negative impacts on the environment and human health [20][21][22][23]. In the following, the related studies are mainly reviewed from three aspects: (1) impacts of SECA on the shipping industry, (2) emission abatement methods from ships, (3) emission regulations for maritime.…”
Section: Literature Reviewmentioning
confidence: 99%